Critical periods for language acquisition: New insights with particular reference to bilingualism research. Issue 5 (23rd October 2018) - ABUTALEBI, JUBIN; CLAHSEN, HARALD
Abstract : One of the best-known claims from language acquisition research is that the capacity to learn languages is constrained by maturational changes, with particular time windows (aka 'critical' or 'sensitive' periods) better suited for language learning than others. Evidence for the critical period hypothesis (CPH) comes from a number of sources demonstrating that age is a crucial predictor for language attainment and that the capacity to learn language diminishes with age. To take just one example, a recent study by Hartshorne, Tenenbaum and Pinker (2018 ) identified a 'sharply-defined critical period' for grammar learning, and a steady decline thereafter, based on a very large dataset (of 2/3 million English Speakers) that allowed them to disentangle critical-period effects from non-age factors (e.g., amount of experience) affecting grammatical performance. Other evidence for the CPH comes from research with individuals who were deprived of linguistic input during the critical period (Curtiss, 1977 ) and were consequently unable to acquire language properly. Moreover, neurobiological research has shown that critical periods affect the neurological substrate for language processing, specifically for grammar (Wartenburger, Heekeren, Abutalebi, Cappa, Villringer & Perani, 2003 ).